Lao PDR Economic Monitor, May 2011 : Robust Growth amidst Inflationary Concerns - World Bank (World Bank, Vientiane, 2017)
Lao PDR's real Gross Domestic Product (GDP) growth will remain robust in 2011 with projected growth of 8.6 percent compared to 8.4 percent in 2010. Natural resources and manufacturing sectors are expected to drive growth this year. The expected growth in the garment exports (by about 15-20 percent in this year) follows the European Union (EU) relaxation in raw material sourcing requirement and increased orders by key garment producers. The service sector also shows signs of improvement, particularly in transport, tourism (hotels and restaurants) and retail trading. Agriculture (fishery, livestock and crops) is expected to benefit from the recent increase in regional demand and higher food prices. Out of 8.6 percent growth in 2011, about 3.6 percentage points come from the resource sectors, about 1 percentage point each from manufacturing and agriculture, 0.5 percentage points from construction and 2.5 percentage points from services. Although overall trade balance is expected to improve the current account deficit is expected to widen slightly too about 9.4 percent of GDP in 2011 from about 8.6 percent in 2010 mainly on the account of larger transfers of profits and debt service payments abroad by large resource projects. Thus, resource current account surplus is expected to decrease to 4.8 percent of GDP in this year from about 5.5 percent in 2010.